(untitled) (Research, Society and Development, 2022)
Modernity creates new trends that promote demands from consumers and manufacturers, and beer production was no different. In search of greater perceptual complexity, non-conventional yeasts emerge as alternatives for enriching the beverage’s attributes. The use of non-Saccharomyces in the fermentation process has provided a greater presence of higher alcohols, esters and volatile phenols, in addition to carboxylic acids and aldehydes, which originate a sensory bouquet. In this context, this work aims to present a literature review regarding the aromatic profile of beers using non-conventional yeasts under isolated or mixed fermentation. The survey was carried out in an international journal between the years 2016 to 2022, in which nine articles on the subject were obtained. The selected studies studied eight genera (Torulaspora, Pichia, Brettanomyces, Hanseniaspora, Zygotorulaspora, Zygoascus, Kazachstania and Saprochaete) and fourteen species of microorganisms. As a result, the ability to assimilate sugars, temperature tolerance and resistance to ethanol stand out. It was identified that different substances provide different odors, among them, fruity, floral and sweet are predominant, in addition to alcoholic notes, cereals, green leaves, among others. Unpleasant odors were also noted due to the concentration of diacetyl and methional, giving rise to aromas of butter, cooked vegetables and rancidity. Therefore, the review becomes a tool to understand the relevant yeasts and which ones are suitable for the desired beer style.